Factors influencing childhood immunisation uptake in Africa: a systematic review - Abubakar Nasiru Galadima; Nor Afiah Mohd Zulkefli; Salmiah Md Said; Norliza Ahmad (BMC, 2021)
Abstract Background Vaccine preventable diseases are still the most common cause of childhood mortality, with an estimated 3 million deaths every year, mainly in Africa and Asia. An estimate of 29% deaths among children aged 1-59 months were due to vaccine preventable diseases. Despite the benefits of childhood immunisation, routine vaccination coverage for all recommended Expanded Programme on Immunization vaccines has remained poor in some African countries, such as Nigeria (31%), Ethiopia (43%), Uganda (55%) and Ghana (57%). The aim of this study is to collate evidence on the factors that influence childhood immunisation uptake in Africa, as well as to provide evidence for future researchers in developing, implementing and evaluating intervention among African populations which will improve childhood immunisation uptake. Methods We conducted a systematic review of articles on the factors influencing under-five childhood immunisation uptake in Africa. This was achieved by using various keywords and searching multiple databases (Medline, PubMed, CINAHL and Psychology & Behavioral Sciences Collection) dating back from inception to 2020. Results Out of 18,708 recorded citations retrieved, 10,396 titles were filtered and 324 titles remained. These 324 abstracts were screened leading to 51 included studies. Statistically significant factors found to influence childhood immunisation uptake were classified into modifiable and non-modifiable factors and were further categorised into different groups based on relevance. The modifiable factors include obstetric factors, maternal knowledge, maternal attitude, self-efficacy and maternal outcome expectation, whereas non-modifiable factors were sociodemographic factors of parent and child, logistic and administration factors. Conclusion Different factors were found to influence under-five childhood immunisation uptake among parents in Africa. Immunisation health education intervention among pregnant women, focusing on the significant findings from this systematic review, would hopefully improve childhood immunisation uptake in African countries with poor coverage rates.